An Analysis of Deixis in Snow White and The Huntsman Movie Script - Alfathmy, Alfathmy; Nurjanah, Anisa (English Language and Literature, 2024)
This study aims to find the types of deixis and deixis references in the Snow White and the Huntsman movie. This study was conducted using a descriptive qualitative method. The data were taken from conversations based on the main characters and minor characters in the Snow White and the Huntsman movie and the data source was the Snow White and the Huntsman movie script. This study used Levinson's theory (1983) to classify the types of deixis and Yule’s theory (1996) to find deixis referents. The data revealed 170 conversations based on the Types of Deixis . Then, the types of deixis that dominant occurred were Personal Deixis as much as 90 times (52.94%). Then, the lowest frequency occurred in Time Deixis. It occurred 9 times (5.30%). In addition, 55 conversations based on Referents of Deixis occurred in Snow White and The Huntsman movie. The dominant frequency was Referential Use. It occurred 19 times (34.54%) and the least occurrence was Attributive Use. The frequency is 5 times (9.09%).